Kepastian Hukum Dari Penerapan Ketentuan Batas Waktu Pengajuan Upaya Hukum Verzet (Studi Terhadap Putusan Pengadilan Negeri Jakarta Barat Nomor 9/Pdt.Plw./2017/PN..JKT.BRT. Jo. Putusan Pengadilan Tinggi Dki Jakarta Nomor 107/Pdt/2018/PT.DKI) - Jonathan Santandrea; Ning Adiasih (Fakultas Hukum Universitas Tarumanagara, 2019)
As state of law, Indonesia must guarantee legal certainty in all fields including the Civil Procedure Code. Legal certainty is achieved if the rule cannot be interpreted differently and is contained in the realization of the consistency of each judge's decision. The time limit for the submission of verzet has been regulated in Article 129 Paragraph (2) HIR. However, the verdict used as study material contained inconsistencies in the decisions of judges between West Jakarta District Court in case number 9 / Pdt.Plw / 2017PN.JKT.BRT. and Jakarta High Court in case number 107 / Pdt / 2018 / PT.DKI Both have different ratio decidendi. What is the legal certainty of applying the deadline for submitting verzet legal remedies? The author uses normative legal research methods and uses interview data as supporting data. The results of the study revealed that there was no legal certainty in the application of the time limit for submitting verzet legal remedies, especially in the condition of the verstek verdict being delivered to the defendant through the village head. The legal consequence is that there are variations in the decision dictum on this matter so that it harms the plaintiff and obscures the meaning of the verstek case which is said to have been inkracht van gewijsde. It is recommended that in the revision of the Civil Procedure Law there are specific guidelines on how to calculate the deadline for submitting verzet in terms of volunteering verstek to be entrusted to the village head.